Focused ultrasound for treatment of uterine myoma: From experimental model to clinical practice - Terzić Milan (Srpski Arhiv za Celokupno Lekarstvo, 2008)
It is well known that focused ultrasound has a biologic effect on tissue. High intensity focused ultrasound (HIFU) on a small target area raises the temperature of the tissue enough to denaturate proteins and cause irreversible cell damage. The tight focus of the ultrasound energy allows delivery of the intended dose to a very precise location. The resulting coagulation necrosis is relatively painless. The application of this method in the human clinical setting has required pilot studies on an animal model. Although the treatment had a high success rate, there was a significant percentage of complications, mainly attributed to the technical drawbacks of the procedure. Therefore, this method has been modified for use in humans, and the HIFU is now guided, monitored and controlled by magnetic resonance imaging (MRI). In October 2004, Food and Drug Adiministration (FDA) approved MRI guided focused ultrasound treatment of uterine fibroids in humans. Since then, successful treatment of uterine myomas by HIFU has been performed in thousands of women.